If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 26 = 9x + 54 Reorder the terms: 26 + 2x = 9x + 54 Reorder the terms: 26 + 2x = 54 + 9x Solving 26 + 2x = 54 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 26 + 2x + -9x = 54 + 9x + -9x Combine like terms: 2x + -9x = -7x 26 + -7x = 54 + 9x + -9x Combine like terms: 9x + -9x = 0 26 + -7x = 54 + 0 26 + -7x = 54 Add '-26' to each side of the equation. 26 + -26 + -7x = 54 + -26 Combine like terms: 26 + -26 = 0 0 + -7x = 54 + -26 -7x = 54 + -26 Combine like terms: 54 + -26 = 28 -7x = 28 Divide each side by '-7'. x = -4 Simplifying x = -4
| 8c^2+14c+3= | | 5w-16=6-5w | | x(4/7)-6=11/7x | | 6x=3x-3 | | 7x+7=8(x+2) | | -69/-3= | | -165=-5(-8n-4)-3n | | -69/-3 | | Y/1-3/4=19/2 | | 6x=7(7x+2) | | -3p+8=5-7p+4 | | k^4+7k^3-30k^2= | | 22=8m+3m | | -78p+2p-5p+8+48= | | 3f-2g=7+hforg | | 3x-5=10-5x | | 2z+(-10)=-19 | | y/1-3/4 | | 11y-36+63= | | -5x-x=6 | | -9(5r-3s)= | | x=7(176)-x | | ak^2-11ak+18a= | | 5m-5=-2+5+9m | | X+bc=5 | | 9x^3=10 | | 4x-17+137= | | 2.1=x/2 | | 3(x-4)+8x=19-2(x+3) | | -7/11x=-2 | | 2-(x-1)=5x+9 | | 8k^3-162k= |